1979
DOI: 10.1007/bf01907684
|View full text |Cite
|
Sign up to set email alerts
|

Experimental coronary artery occlusion

Abstract: We studied the size of infarcts in 25 dogs 48 hrs after proximal occlusion of the left anterior descending coronary artery. In one group of animals infarct size was measured by histologic criteria, in another group the infarct was measured macrohistochemically using p-NBT and malate to incubate unfixed slices of myocardium. In both groups infarct size was expressed as percentage of the area of perfusion of the occluded artery. Infarct size was 72% of the area-at-risk in the group studied by histology and 74.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 8 publications
2
54
0
Order By: Relevance
“…The boundaries of the involved vascular bed were determined from x-rays of serial cross sections of the ventricles after postmortem coronary injection with barium sulfate suspensions. Similar techniques have been used by others.7 [24][25][26][27] The study demonstrated a close linear correlation between infarct size and the size of the vascular bed. Thus, in humans as in dogs, ischemic bed size is a major determinant of infarct size.…”
Section: Variation Of Infarct Size Within the Vascular Bed At Risksupporting
confidence: 53%
“…The boundaries of the involved vascular bed were determined from x-rays of serial cross sections of the ventricles after postmortem coronary injection with barium sulfate suspensions. Similar techniques have been used by others.7 [24][25][26][27] The study demonstrated a close linear correlation between infarct size and the size of the vascular bed. Thus, in humans as in dogs, ischemic bed size is a major determinant of infarct size.…”
Section: Variation Of Infarct Size Within the Vascular Bed At Risksupporting
confidence: 53%
“…Accordingly, the primary therapeutic strategy to reduce cardiovascular mortality is reduction of infarct size (IS). IS increases with coronary artery occlusion time, myocardial area at risk for infarction (AR), lack of collateral supply, absence of preconditioning, and myocardial demand for O 2 (i.e., the product of contractility, heart rate, and ventricular wall stress) (16,18).…”
mentioning
confidence: 99%
“…[1][2][3] Similarly, for a given RA size and duration of coronary occlusion, IS depends on the magnitude and spatial extent of residual collateral-derived MBF. [1][2][3] Currently, IS can be measured by myocardial contrast echocardiography (MCE) only after reperfusion, by exploiting the "no-reflow" state of necrotic tissue. 4 -8 In this setting, fewer microbubbles enter the necrotic zone because of functional and/or structural damage to the capillaries.…”
mentioning
confidence: 99%